Selective terminal C–C scission of C5-carbohydrates1. Issue 7 (6th July 2015) - van der Klis, Frits; Gootjes, Linda; van Haveren, Jacco; van Es, Daan S.; Bitter, Johannes H.
<x xml:space="preserve">Abstract</x> Selective terminal C–C scission of non-edible C5-carbohydrates over Ru/C to C4-polyol building blocks was achieved under mild reaction conditions (138 °C, 6 bar H2).